Changes of historical metadata reflected in the wind parameters at Iași meteorological station - George-Stelian Tudorache; Nicoleta Ionac; Bogdan Maco; Ancuța Manea (Present Environment and Sustainable Development, 2017)
The metadata are defined as the informations behind the data. The purpose of the metadata in meteorological activity is to represent where, when, how and by whom meteorological data has been obtained, colected and recorded. Ideally, a comprehensive metadata base should contain records of all changes that have occured throughout the entire period in which the meteorological station has functioned, the so called „station history”. This paper renders the preliminary results of the analysed wind parameter values (percentages of wind calm and wind frequency) for the time period between 1961 and 2015 at Iași meteorological station. The data were analysed based on various historical metadata information (e.g. the emergence of new construction(s) around the station, relocation of the station, changes in the equipment used to measure the wind etc.), information that may influence the wind parameters measured at Iași weather station.